An ethical diagnosis of proverbs 6:6-8 about leadership failure in Nigeria (2025)
The bane of growth in the nation's political trajectory has been caused by leadership failure and its impact on the populace. Once acknowledged and revered as Africa's developmental power house in all respects, Nigeria has lost its pride due to selfish leaders and avaricious followers who always prioritise their interests over the good of the whole. The process of motivating, directing, and persuading people to realise a common Vision, aim, or objective is known as leadership. A proactive approach, activity, or attitude that motivates and sways others to accomplish a particular objective is more important than a title. It is the capacity to guide and lead a team towards a goal successfully. Sadly, the Situation is the exact opposite in Africa, and Nigeria in particular, where the ruling elite has transformed the nation into a conduit through which our Commonwealth is being greedily siphoned for the benefit of themselves and their progeny. Scholarly works that have already been written about leadership in Nigeria have mostly focused on how Nigerian leaders have shaped the nation 's development since its independence, with little attention paid to the importance of Proverbs Chapter 6:6—8, which offers an ethical diagnosis of the social, political, and economic Problems arising from the nation's political leaders' incompetence, ignorance, carelessness, and irresponsibility. From a methodological standpoint, the research employed qualitative methods to gather data. According to the paper's results, leadership failure has caused the African continent to fall behind other developed nations, and the advice given by Solomon in Proverbs 6:6-8 can help address the region's plethora of issues and take her back to its Position as a giant of Africa indeed.